2021
DOI: 10.1371/journal.ppat.1009598
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial tyrosine phosphatase modulates cell proliferation through targeting RGCC

Abstract: Tyrosine phosphatases are often weaponized by bacteria colonizing mucosal barriers to manipulate host cell signal transduction pathways. Porphyromonas gingivalis is a periodontal pathogen and emerging oncopathogen which interferes with gingival epithelial cell proliferation and migration, and induces a partial epithelial mesenchymal transition. P. gingivalis produces two tyrosine phosphatases, and we show here that the low molecular weight tyrosine phosphatase, Ltp1, is secreted within gingival epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…In summary, SerB can promote bacterial invasion of the host, allowing it to continue to exert its full pathogenic potential. Interestingly, it has very recently been reported that the tyrosine phosphatase (Ltp1) can also be secreted by P. gingivalis and appears in both the cytoplasm and nucleus of gingival epithelial cells ( Liu et al., 2021 ). The secreted Ltp1 can bind to phosphatase and tensin homolog (PTEN) and dephosphorylate its Y336 residue, resulting in the degradation of PTEN.…”
Section: The Function Of Oral Bacterial Tyrosine and Serine/threonine Kinases And Phosphatasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, SerB can promote bacterial invasion of the host, allowing it to continue to exert its full pathogenic potential. Interestingly, it has very recently been reported that the tyrosine phosphatase (Ltp1) can also be secreted by P. gingivalis and appears in both the cytoplasm and nucleus of gingival epithelial cells ( Liu et al., 2021 ). The secreted Ltp1 can bind to phosphatase and tensin homolog (PTEN) and dephosphorylate its Y336 residue, resulting in the degradation of PTEN.…”
Section: The Function Of Oral Bacterial Tyrosine and Serine/threonine Kinases And Phosphatasesmentioning
confidence: 99%
“…PTEN is a classic negative regulator of phosphoinositide 3-kinases/protein kinase B (PI3K/Akt). Thus, the inhibition of PTEN by Ltp1 could further activate PI3K/Akt and its downstream regulator of the cell cycle (RGCC), promoting the migration, proliferation and epithelial mesenchymal transition of epithelial cells ( Liu et al., 2021 ) ( Figure 5 ).…”
Section: The Function Of Oral Bacterial Tyrosine and Serine/threonine Kinases And Phosphatasesmentioning
confidence: 99%
“…Bacterial LMW-LTPs can also be secreted by yet to be defined mechanisms [ 42 , 43 ], and in the case of PtpA of Mycobacterium tuberculosis , enter into host cell nuclei [ 43 ]. P. gingivalis can also introduce Ltp1 directly into gingival epithelial cells where it can translocate to the nucleus [ 44 ]. As Ltp1 lacks the consensus sequence for recognition by the Type IX secretion system, the secretion process remains to be established.…”
Section: Tyrosine Kinase and Phosphatase Functions In P Gin...mentioning
confidence: 99%
“…An intracellular location will protect the enzyme from inactivation by metabolites such as pABA and peroxide produced by other organisms in the extracellular environment. Intracellular Ltp1 dephosphorylates PTEN on Y336 which results in elevated proteasomal degradation [ 44 ]. Reduced PTEN levels cause an increase in signaling through the PI3K-Akt pathway which converges on transcriptional upregulation of Regulator of Growth and Cell Cycle (RGCC) ( Figure 2 ).…”
Section: Tyrosine Kinase and Phosphatase Functions In P Gin...mentioning
confidence: 99%
“…Specifically, periodontitis, which is an inflammatory disease that is initiated by the dysbiosis of oral flora, is characterized by the destruction of alveolar bone and connective tissues around the teeth ( Liu et al., 2017b ; Lu et al., 2020 ; Hajishengallis and Lamont, 2021 ). It has also been suggested that Porphyromonas gingivalis , a gram-negative anaerobe, is the most important pathogenic bacterium in periodontitis ( Lamont et al., 2018 ; Liu et al., 2021 ). Furthermore, P. gingivalis possesses a plurality of virulence factors that invade periodontal tissues and subsequently enter blood circulation and disseminate into the whole body, increasing the risk of several systemic diseases, notably diabetes, cardiovascular diseases, rheumatoid arthritis, Alzheimer’s disease, and NAFLD ( Potempa et al., 2017 ; Nakahara et al., 2018 ; Mei et al., 2020 ; Fitzsimonds et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%